The Effect of Islamic Finance on Economic Growth and Financial Stability: ASEAN-4 Case Study - Hanif, Azianatud Dian; Hanafi, Syafiq Mahmadah (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2023)
This research aims to analyze the impact of Islamic finance (Islamic stock index and sharia banking assets) on economic growth and financial stability. The data utilized in this study are panel data from the ASEAN-4 countries during the period 2013-2022, employing panel data regression analysis with the Common Effect Model. The research findings indicate that simultaneously, the independent variables significantly affect economic growth and financial stability in the ASEAN-4 countries during the period 2013-2022. Partially, the Islamic stock index variable does not have a significant impact on economic growth but has a significant impact on financial stability. Meanwhile, the sharia banking assets variable significantly affects economic growth but does not significantly affect financial stability.